Pradhan Mantri Jan Dhan Yojana (PMJDY):A Step towards Eradicating Financial Untouchability - Verma, Yogesh; Garg, Priyanka (Indian Journal of Finance, 2016)
Financial untouchability is a phenomenon that results from certain situations that prevents people to access formal financial systems. In the absence of a formal financial system, people are forced to go to local money lenders who charge exorbitant interest rates from poor people. Financial untouchability also creates the problem of social discrimination. The only solution to fight with the evil of financial untouchability is promotion of financial inclusion, which may be defined as the process of ensuring access to financial services and timely and adequate credit where needed by vulnerable groups such as weaker sections and low income groups at an affordable cost. Financial inclusion can be achieved by ensuring access to financial services, affordability of services, and actual utilization of financial services. In order to promote financial inclusion, the Pradhan Mantri Jan Dhan Yojana (PMJDY) was launched across the country. It is a mission mode project of the Government of India. The scheme aims to ensure universal access to banking facilities in each and every household of the country. The scheme has provision of opening a zero balance account with free debit card and inbuilt accidental insurance. It also includes program of financial literacy, access to credit, and insurance facility. The present study made an attempt to study the effectiveness of PMJDY by analyzing the effectiveness of the financial literacy program and awareness towards PMJDY. The study was carried out among workers in working in Central University of Rajasthan and villagers of Bandrasindri village in Ajmer district of Rajasthan. The primary data was gathered in the form of discussions held with respondents in 2015. The secondary data were collected from various published and non-published sources. The findings of study showed that still, there is a long path which needs to be covered to eradicate financial untouchability in a real sense from our country.